Tailoring strength-ductility synergy in Ce-doped lightweight Nb0.5TiZrV0.5 refractory high entropy alloy: phase transformation-controlled deformation mechanisms at 600 °C and 800 °C - Haili Yao; Youxing Yu; Jiangbo Sha (Journal of Materials Research and Technology)
The lightweight Nb0.5TiZrV0.5 refractory high-entropy alloys (RHEA) doped with Ce were prepared by arc melting (AM). The precipitating evolution in grain interior (GI) and grain boundary (GB), the tensile mechanical properties and the deformation mechanisms including dislocation configuration, kink band evolution and/or interaction between dislocation and precipitate of the AM (Nb0.5TiZrV0.5)100-xCex RHEAs (at.%, x = 0, 0.005, 0.01, referred to as 0Ce, 0.005Ce and 0.01Ce alloys) during tension at 600 °C and 800 °C were systematically investigated. The 0.005Ce alloy exhibits the most significant grain refinement effect. Segregation of the Ce was observed at GBs, accompanied by a phase transformation from the BCC band (Ce-, V-rich but Zr-poor) in the 0.005Ce alloy to the ω-like phase (Ce-, V- and Zr-rich but Ti-poor) in the 0.01Ce alloy. The 0.005Ce alloy exhibited an optimized yield strength-fracture strain match (σ0.2∼225.8 MPa, FS∼23.05 %) at 800 °C, due to the highest volume fraction (49.1 %) of elliptical BCC1 phase in GIs, the BCC2 phase and the discontinuous α phase (hexagonal close packed (HCP)) at GBs, and the highest fraction (37.5 %) of <111> {110} non-screw dislocations in the fracture planes formed during deformation. At 600 °C, however, the 0.005Ce alloy exhibited medium yield strength-ductility matching (σ0.2∼759.3 MPa, εf∼4.28 %), because of the BCC bands at GBs, more <111> {110} and <111> {123} non-screw dislocations and kink bands arisen during deformation. These results may provide guidance for design of the lightweight RHEAs better strength and ductility through doping Ce or other rare-earth elements.